The effect of discovery learning integrated with Lampung local wisdom on students’ mathematical problem-solving skills across gender - Munafiroh, Verawati; Kawuryan, Sekar Purbarini; Munawwarah, Siti (Jurnal Penelitian Ilmu Pendidikan, 2024)
Mathematical problem-solving skills remain a persistent challenge for elementary students, partly due to the lack of contextual learning approaches that connect mathematics with local culture. However, limited empirical evidence examines whether integrating local wisdom into learning models can enhance students’ problem-solving performance across gender. This study aimed to analyze the effect of Discovery Learning integrated with Lampung local wisdom on students’ mathematical problem-solving skills and to examine whether this effect differs by gender. Using a quasi-experimental 2×2 factorial design, this study involved 41 fifth-grade students at a public elementary school in Pesisir Barat Regency, selected through random sampling. Data were collected using a validated problem-solving test and analyzed using two-way ANOVA. The results indicated that: (1) the learning model had a significant effect on problem-solving skills, (2) there was no significant difference between male and female students, and (3) no interaction effect was found between learning model and gender. These findings highlight the effectiveness of culturally integrated Discovery Learning in improving students’ mathematical problem-solving skills in an inclusive manner. The study contributes to the growing literature on culturally responsive mathematics instruction and encourages educators to use local-wisdom-based approaches to support equitable 21st-century skill development.